Labour market expectations of University of Technology graduates in human resource management: implications for programme planning - Ncokazi, Tebogo Abram (University of the Free State, 2016)
Globally, the field of Human Resource Management (HRM) evolved from a support endeavour into a strategic counterpart for the effective functioning of organisations. The evolution of HR has determined various changing roles in the field. HR basically has reacted to external challenges and constant changes such as technological advances, globalisation and dwindling economies globally, a competitive market environment, increasing organisational complexity, increased external competition, reduced budgets and tougher demands from business. This study investigates the evolution of human resource management competencies, knowledge and attributes, and how these changes dictate the manner in which HR curricula need to change in order to be responsive to the needs of the South African labour market and elsewhere in the world. This also takes cognisance of the fact that the world has become a global village, and therefore organisations operate across the global spectrum. HR curricula in institutions of higher learning, especially the universities of technology (UoTs) need to adapt and include the HR qualities that the world of work perceive as fundamental in the execution of duties of HR professionals and the training of HR students. The revised and reformed HRM curriculum and subsequent changes ideally will reflect changing knowledge and competencies, and required attributes being aligned with the professional requirements demanded by the world of work. This study, therefore, focused on several HR competency models and relevant competencies and skills sets, as well as attributes that were exposed as meeting the evolving world of work. The researcher applied a qualitative analysis that involves a process of designing condensed raw data into categories or themes based on valid inferences and interpretation. This enabled the analysis of HR job requirements, since a purposeful sample of organisations in the South African labour market had been selected. The data were coded and analysed to identify core consistencies and meanings, revealing those competencies and skills, knowledge and attributes that characterise the contemporary HR specialist. The identified characteristics, competencies and skills sets, as well as behavioural attributes that reflect an ‘ideal’ HR professional and HR graduate were scrutinised in terms of the perceived HR requirements indicated by the world of work. This was done with the purpose of recommending the linkage of HR requirements according to the perception of the labour market to the curriculum design and planning of HR training programmes in higher education institutions. This also was done to elucidate to the higher education institution what needs to inform HR training in terms of the development of knowledge, competencies and attributes to be responsive to the requirements of the world of work. This study finally integrates the criteria and requirements for higher education qualifications with the demands of the profession and accordingly illustrates how the curriculum could balance academic knowledge, societal pressures and employer needs and thus produce graduates who fulfil a responsible role in the global field of HR profession.

Die veld van menslikehulpbronbestuur het wêreldwyd ontwikkel van ’n ondersteuningstrewe tot ’n strategiese genoot in die strewe na effektiewe funksionering in organisasies. Die evolusie van menslike hulpbronne (MH) het verskeie veranderende rolle op die terrein bepaal. MH het basies gereageer op eksterne uitdagings en voortdurende veranderinge soos tegnologiese vooruitgang, globalisering en verskrompelende ekonomieë reg deur die wêreld; ŉ mededingende markomgewing, toenemende organisatoriese kompleksiteit, ŉ toename in eksterne wedywering, krimpende begrotings en dwingender eise vanuit die sakewêreld. In die studie is die evolusie van die kompetensies vir menslikehulpbronbestuur ondersoek, asook hoe dié veranderinge die wyse voorskryf waarop MH-kurrikula moet verander ten einde gehoor te gee aan die behoeftes van die Suid-Afrikaanse arbeidsmark en ook elders in die wêreld. Hierin word dit ook in ag geneem dat die wêreld ŉ aarddorp geword het; dus opereer organisasies regoor die globale spektrum. MH-kurrikula aan hoëronderwysinstellings, veral aan die universiteite vir tegnologie, sal moet aanpas en die MH-kwaliteite wat deur die arbeidsveld as grondliggend beskou word vir die uitvoering van die pligte van professionele menslikehulpbronbestuurders en die opleiding van MH-studente, insluit. Die ideaal is dat die hersiene en aangepaste MHB-kurrikulum en die daaruit voortspruitende veranderinge belyning moet weerspieël van die veranderende kennis en kompetensies met die professionele vereistes van die arbeidsveld. Die studie het dus die fokus geplaas op verskeie MH-kompetensiemodelle en -vaardighede, en eienskappe is blootgelê wat voldoen aan die evolusie in die arbeidsveld. Die navorser het van kwalitatiewe analise gebruik gemaak wat ŉ proses van omsetting van rou data in kategorieë of temas, gebaseer op geldige afleidings en interpretasies, behels. Dit het dit moontlik gemaak om MH-posvereistes te analiseer, aangesien ŉ monster van organisasies in die Suid-Afrikaanse arbeidsmag doelgerig geselekteer is. Die data is gekodeer en geanaliseer om kernkonsekwensies en -betekenisse te identifiseer, en daardeur is die kompetensies en vaardighede, kennis en eienskappe wat die kontemporêre MH-spesialis kenmerk, blootgelê. Die geïdentifiseerde eienskappe, kompetensies en vaardighede, sowel as die gedragskenmerke wat die ‘ideale’ professionele MH-praktisyn en -gegradueerde weerspieël, is deeglik bestudeer met betrekking tot waarneembare MH-vereistes soos aangedui deur die arbeidsveld. Dit is gedoen met die oog daarop om die koppeling van MH-vereistes volgens die persepsie van die arbeidsmark met kurrikulumontwerp en -beplanning vir MH-opleiding aan hoëronderwysinstellings aan te beveel. Dit is ook gedoen om vir hoëronderwysinstellings lig te werp op wat gedoen moet word om MH-opleiding beter toe te rus ten opsigte van die ontwikkeling van kennis, kompetensies en eienskappe ten einde te voldoen aan die vereistes van die arbeidsveld. In die finale instansie word die kriteria en vereistes van hoëronderwyskwalifikasies in die studie met die vereistes van die professie geïntegreer en illustreer dit hoe die kurrikulum akademiese kennis, gemeenskapsdruk en werkgewerbehoeftes kan balanseer, en sodoende gegradueerdes kan lewer wat ŉ verantwoordelike rol kan vervul op die globale terrein van die professie van menslikehulpbronbestuur.
Thesis (Ph.D. (School of Higher Education Studies))--University of the Free State, 2016
Keywords: Curriculum design; Human resource management; Labour market; Curriculum planning; Labor market -- South Africa